Green building development utilising modified fired clay bricks and eggshell waste - Wafaa Soliman; Yasser M. Z. Ahmed; Ahmed Ghitas; Abdel‑Hamid El‑Shater; M. Abdelhamid Shahat (Scientific Reports)
Abstract The inadequate thermal insulation of the building envelope contributes significantly to the high power consumption of air conditioners in houses. A crucial factor in raising a building’s energy efficiency involves utilizing bricks with high thermal resistance. This issue is accompanied by another critical challenge: recycling and disposing of waste in a way that is both economically and environmentally beneficial, including using it to fuel industrial growth, in order to reduce the harmful effects of waste on the environment as waste generation in our societies grows. To this end, the current study sought to assess whether integrating a specific amount of eggshell waste as CaCO3 filler within bricks consistently produces fired clay bricks with desirable thermal insulation capabilities. By systematically investigating the physicochemical and thermal characteristics of bricks doped with varying eggshell content, this work demonstrates how waste materials can be repurposed to produce sustainable construction materials with superior performance. The results highlight significant improvements in thermal conductivity, diffusivity, and effusivity, alongside favorable changes in porosity, bulk density, and mechanical strength. The XRD analysis revealed that once the firing temperature rises, a high insulation feature arises due to siliceous melt formation. EDX analysis gave important insights into the impact of eggshell dopants on the physicochemical parameters of burnt clay bricks. Compared to pristine brick, CEs7% brick constructed with clay and 7 wt% eggshell exhibited a 38.7% loss on dry shrinkage, an enhancement on average pore size of 78.8%, an apparent porosity of 52.7%, a bulk density of 8.3%, and a compressive strength of 57.5%. The reduced shrinkage enhances stability, while increased pore size and porosity improve thermal insulation, making the bricks more durable and energy-efficient. In this regard, the brick containing 10% eggshell that was fired at 1100°C possessed the greatest drop in heat conductivity (i.e., 50%), thermal diffusivity (30%), and thermal effusivity (30%) as compared to the pure one. Given the aforementioned findings, these additions hold the potential to reduce the energy required for both heating and cooling buildings. This brings us to the conclusion that combining eggshell waste to create calcium silicate makes it feasible to be utilized as a thermal insulation material, paving the way for improved construction materials’ performance and sustainability.